Experiences and Strategies of Women in STEM in Leadership Positions and Hybrids in the IT Sector - Martínez Gómez, Rosa (2022)
Gender  stereotypes  represent  an  important  factor  in  the  vocational  choice  of  women  in  Chile.  This  has  been  more  evident  in  STEM  careers,  historically  masculinized.  This  masculinization  was  transferred  to  the  industry,  especially  in  leadership  positions  in  information technology. In Chile, although some women work in this field, only a few of them  lead  technological  teams  or  processes  in  national  companies.  The  objective  of this qualitative research is to determine what cultural, socioeconomic, educational and personal aspects have in common the Chilean women in STEM careers who managed to position themselves in leadership positions in local companies. The study establishes a  common  pattern  in  the  profile  of  these  women:  resilience  in  the  face  of  adverse  environments and situations, empowerment to achieve their professional goals and the importance of support networks to outsource domestic and care work.